Sector Field Mass Spectrometry for Elemental and Isotopic Analysis 2014
DOI: 10.1039/9781849735407-00107
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Isotopic Fractionation

Abstract: In mass spectrometry, the term ‘instrumental isotopic fractionation’ is recommended to describe the sum of the effects in a mass spectrometer occurring during sample introduction, ion formation, ion extraction, ion separation and ion detection leading to a difference of the measured isotope ratio from the true isotope ratio in a sample. Instrumental isotopic fractionation (IIF) describes the instrumental fractionation between nuclides of the same element resulting in erroneous results of isotope ratios. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Throughout the present study, measurement precision under different specied conditions of measurement are considered: 45 (i) isotope ratio precision (aka internal precision), expressed as RSD, refers to the standard deviation of M runs averaged to one measurement result, (ii) repeatability is the standard deviation of N measurements taken within a short time period, and (iii) intermediate precision is the standard deviation of N measurements over several days and used here as a measure for long-term stability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the present study, measurement precision under different specied conditions of measurement are considered: 45 (i) isotope ratio precision (aka internal precision), expressed as RSD, refers to the standard deviation of M runs averaged to one measurement result, (ii) repeatability is the standard deviation of N measurements taken within a short time period, and (iii) intermediate precision is the standard deviation of N measurements over several days and used here as a measure for long-term stability.…”
Section: Methodsmentioning
confidence: 99%
“…35,37 This external IIF correction model can correct for mass dependent and mass independent IIF. 35 Taking a closer look at IIF, 34,41 previous studies using the rst generation of ICP-TOFMS reported that the IIF per mass unit is substantial for light elements (e.g., Li has −13%) whereas for high mass elements the IIF per mass unit is signicantly lower (e.g., Pb has 0.2%). 24 This is similar to observations from MC ICP-MS and ICP-QMS measurements, where the IIF typically varies systematically from about −13% to −15% for Li to −0.2% for U.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ICP-MS, the ionization source and the interface are believed to play a major role in IIF, mainly due to the large pressure drop between the ion source and the expansion region. These phenomena have recently been described in more detail for ICP-MS, GDMS, TIMS, SIMS and IRMS [17].…”
Section: Measurement Related Factorsmentioning
confidence: 99%
“…Today, MC ICP-MS allows determining isotope ratios with measurement precisions comparable to those of TIMS (down to 0.001%) [10]. This might include preparatory work to fully separate the analyte isotopes from the matrix in order to overcome systematic errors derived from matrix-induced interferences as well as changes in instrumental isotopic fractionation (aka mass bias), which is significantly larger for MC ICP-MS [14][15][16] than for TIMS [12,17,18].…”
Section: As a Consequence Isotope Ratio Analysis Via MC Icp-ms Has Dmentioning
confidence: 99%